Human evaluation of amphibian species: a comparison of disgust and beauty - Frynta, Daniel; Peléšková, Šárka; Rádlová, Silvie; Janovcová, Markéta; Landová, Eva (Die Naturwissenschaften, 2019)
Animals can evoke a wide range of emotions helping us to choose a quick and appropriate reaction towards them: approach or avoidance in general. This work has focused on disgust evoked by amphibians in humans as well as perceived beauty. Due to the high morphological variability of recent amphibian taxa, we examined humans' cognitive categorisation of 101 amphibian photos and the effect of stimuli characteristics on disgust evaluation or beauty perception of individual groups/species. We also explored how respondents' characteristics, e.g. gender, age and disgust sensitivity (DS-R) influence the disgust and beauty evaluation of picture stimuli on a 7-point Likert scale. The scores of disgust and beauty evaluation were strongly negatively correlated, representing the opposite ends of a single axis, further referred to as the index of preference. The most preferred amphibians belonged to anurans, whereas the least preferred ones were mostly worm-like, legless and small-eyed caecilians. Additional analyses of morphologically diverse anurans showed that species with a round body shape, short forelegs, small eyes, warts, pink and grey colouration, or dark and dull colouration were perceived as disgusting or ugly. The effect of gender and age were only marginal; however, people with higher disgust sensitivity rated amphibians as more disgusting and less beautiful, which might support the hypothesis of a possible disgust involvement in animal fears and phobias. This topic has implications not only for the nature conservation decisions of globally endangered amphibians but also for understanding the evolution of disgust and its generalisation to harmless animals.
Keywords: krása; mužské pohlaví; Beauty; odpor; Animal beauty; Amphibians; ženské pohlaví; zvířata; Humans; Evolutionary psychology; Disgust; Emotions; Phobic Disorders; fobie; Nature conservation; Female; obojživelníci; lidé; Male; Animals